2017
DOI: 10.1080/21645515.2016.1253644
|View full text |Cite
|
Sign up to set email alerts
|

Rapid safety assessment of a seasonal intradermal trivalent influenza vaccine

Abstract: Seasonal influenza vaccine formulations must be updated annually to correspond to the influenza viruses in circulation. This was an uncontrolled, open-label, multi-center phase IV study conducted in Belgium to comply with interim European Medicines Agency (EMA) guidelines for rapidly evaluating the safety of newly formulated seasonal influenza vaccines. Adult volunteers received one dose of the 2014-2015 Northern Hemisphere formulation of licensed intradermal trivalent influenza vaccine at either the standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This seems to suggest that use of ADR cards together with EHR system weekly data extractions is an appropriate tool for adverse event surveillance. Other approaches have been proposed to meet EMA requirements [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that use of ADR cards together with EHR system weekly data extractions is an appropriate tool for adverse event surveillance. Other approaches have been proposed to meet EMA requirements [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12 Four complete influenza seasons have elapsed since the release of the EMA interim and updated guidance on ESS and several groups (i.e., academic groups, public health representatives, and manufacturers) have reported the outcome of their ESS investigations for the following seasons; 2014/15 (two studies), 2015/16 (three studies), 2016/17 (three studies); and 2017/18 (three studies) ( Table 1). Most studies are published [13][14][15][16][17][18][19][20] (or accepted for publication 21 ), and one additional study evaluating GSKs Fluarix Tetra for the 2017/18 (NCT03278067) season is also completed. 22 The vaccines studied were Sanofi Pasteur's Intanza (9 and 15 µg), Vaxigrip and Vaxigrip Tetra, GSK's Fluarix Tetra/ Alpharix Tetra and AstraZeneca's Fluenz Tetra.…”
Section: Changes To Ema Guidancementioning
confidence: 99%
“…Of 11 studies reported here, 9 employed the EPS methodology,1 was set up as a non-interventional voluntary PASS, and 1 was a passive surveillance using a population-based description study design (Table 1). To facilitate passive reporting of AEIs, five of the EPS studies used a combination of Adverse Event Reporting Cards (AERCs) and data from patients' EHR,; 15,17,19,21,22 one study used daily diaries and patient interviews, 13 one used a webbased questionnaire with daily reminders via text message, 18 one used telephone interview 20 , and another principally used telephone interview although a minority used web-based questionnaire. 16 The PASS study employed a web-based questionnaire issued 14 days after vaccination.…”
Section: Changes To Ema Guidancementioning
confidence: 99%
“…In the second group, 54% documented a reaction at the site of application and 32% reported a systemic reaction. In both groups the reactions were mild and transitory [32].…”
Section: Indicationmentioning
confidence: 89%